DEVELOPMENT OF A MANUALLY OPERATED CASSAVA HARVESTER USING HYDRAULIC MEDIUM (FULafia Journal of Science and Technology, 2018)
Cassava harvesting in Nigeria is still a major challenge to many small scale farmers who utilize basic tools and implements in its cultivation. Manual cassava harvesting is difficult and full of drudgery especially during the dry seasons when the soil moisture content is low. The mechanized alternatives are way beyond the reach of resource poor farmers. This research study developed a low cost manually powered harvesting device using a hydraulic ram and plunger system. The major components of the harvester include the base frame, the support stand, lifting arm, lifting medium and the clamp. Some of the design considerations include ease of reproducibility and ability to lift the cassava with minimal damage. The hydraulic power source capable of lifting 5ton of weight was adopted with a human effort of 50N (5 kg). Preliminary evaluation of the device on 20 stands of randomly selected mature cassava stands at 63% soil moisture content recorded a minimum time of 13 seconds and a maximum time of 35 seconds respectively while there was no damage recorded on the tubers and stem girth during the harvsesting procedure as the gradually applied load enusred minimal disturbance was casued to the soil